2014
DOI: 10.1007/s00214-014-1502-9
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of small aromatic molecules on gold: a DFT localized basis set study including van der Waals effects

Abstract: We compare the density functional theory (DFT) results on the adsorption of small aromatic molecules (benzene, pyridine and thiophene) on gold surfaces obtained by using three types of van der Waals exchange-correlation functionals and localized basis set calculations. We show that the value of the molecule-surface binding energy depends on the interplay between the BSSE effect and the tendency of the exchange-correlation functionals to overestimate both the molecule-surface as well as the gold-gold distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 71 publications
5
29
0
Order By: Relevance
“…We used the van der Waals exchange-correlation functional of Berland and Hyldgaard (BH) 41 . During our tests we found that the BH functional correctly describes the geometric structure of the metallic bulks and surfaces which is a major advantage in the study of molecular adsorption 42 .…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…We used the van der Waals exchange-correlation functional of Berland and Hyldgaard (BH) 41 . During our tests we found that the BH functional correctly describes the geometric structure of the metallic bulks and surfaces which is a major advantage in the study of molecular adsorption 42 .…”
Section: Methodsmentioning
confidence: 81%
“…The binding energy for the adsorbed molecules, Δ , was computed by taking into account the BSSE effect as well as the molecular deformation upon adsorption 42 , 46 (see Supplementary material for technical details).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of van der Waals interactions is an important part of this work. They are known to play a role in the adsorption of small aromatic molecules on Au surfaces [ 27 ], the catalytic selectivity for the oxidation of organic molecules on metallic Au [ 28 ], the electronic and energetic properties of small Au NPs [ 29 ], and to be competing with covalent and ionic bonds for bonding on Au–S surfaces and Au NPs [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Weak van der Waals interactions, typically ignored in the presence of covalent bonds, take center stage in determining the favorable adsorption sites on the catalyst surfaces. In addition to catalyst design, noncovalent interactions between organic molecules and planar single crystal metal surfaces have also been recently studied in the context of self-assembled monolayer (SAM) systems and identified as the principal factor in determining the assembly patterns [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%